Acute renal failure in children: outcome and prognostic factors - Partini P Trihono; Ommy A Soesilo; Rulina Suradi (Paediatrica Indonesiana, 2003)
Background Acute renal failure (ARF) is an emergency conditionwith a high mortality rate despite the long-known dialysis and ad-vanced supportive care. Only few studies on prognostic factors ofARF in children are available in the literature, which are difficult tocompare to each other due to the different definitions of the ARFoutcome used.Objective To find out the clinical and laboratory characteristics ofchildren with acute renal failure and the prognostic factors affect-ing the outcome.Methods This observational prospective study was conducted onchildren with acute renal failure hospitalized in the Department ofChild Health, Cipto Mangunkusumo Hospital, between July andDecember 2001. Patients with acute on chronic renal failure wereexcluded. Clinical and laboratory data were taken at the time ofdiagnosis and the outcomes were noted after 2 weeks of observa-tion. We classified the outcome as cured, uncured, and dead. Ana-lytical study was done to find out the relationships among variousprognostic factors.Results Fifty-six children with ARF were recruited in this study.Male to female ratio was 1.3:1; the mean age was 4.4 year-old.The most frequent presenting symptom was dyspnea (34%), fol-lowed by oliguria (29%). The most frequent primary disease wasmalignancy (20%). Most of the patients had renal-type of ARF(73%). The outcomes were cure (71%), no cure (16%), and death(13%). Bivariate analysis and logistic regression revealed thatyounger age (OR=13.6; 95%CI 1.01;183.60) and the need for di-alysis (OR=10; 95%CI 1.53;65.97) had significant relationships withmortality or no cure.Conclusion We should be aware when finding ARF patientsless than 5 year-old and have the indications for dialysis, due tothe poor prognosis they might have